THE EFFECT OF CONTRACTILE ACTIVITY AND SUBSTRATE CHALLENGES ON METABOLIC FLEXIBILITY IN HUMAN PRIMARY MYOTUBES - Weber, Todd M. (East Carolina University, 2013)
The skeletal muscle of severely obese individuals (BMI > 40 kg/m²) is characterized by a depressed ability to oxidize fatty acids and a failure to upregulate fatty acid oxidation (FAO) in response to increased lipid availability, both of which may contribute to a positive lipid balance and weight gain. The inability to switch from predominately glucose oxidation to FAO in the presence of a lipid challenge, such as a high-fat diet (HFD), is part of a defect in obesity known as metabolic inflexibility. In severe obesity, ten consecutive days of aerobic training (short-term training) partially restores metabolic flexibility by increasing the ability of skeletal muscle to oxidize fatty acids. The purpose of this dissertation was to determine a) whether contractile activity in human primary skeletal muscle cell culture (HSkMC) via electrical stimulation provides a model to investigate the mechanisms underlying the ability of short-term aerobic training to normalize FAO and provide some degree of metabolic flexibility in severely obese individuals and b) whether the metabolic inflexibility present in obesity is unique to a lipid challenge such as a HFD or whether obese individuals are also metabolically inflexible when challenged with carbohydrates (CHO) such as galactose or pyruvate. The hypotheses were that 1) HSkMC would provide a model to investigate how in vivo contractile activity increases FAO and markers of mitochondrial content in response to short-term aerobic training and 2) HSkMC from severely obese individuals would be metabolically flexible in response to galactose or pyruvate but would remain metabolically inflexible to a lipid challenge. The results contained herein suggest that contractile activity in HSkMC for 48 h may be capable of mimicking some of the short-term training effects such as increased FAO; however, a longer electrical stimulation period is warranted to initiate changes in mitochondrial content and oxidative capacity. Although comparisons between lean and obese were not made in this study, the results and recommendations of the present investigation have laid the groundwork for future studies to investigate the effect of electrical stimulation on HSkMC established from severely obese individuals. In the second study of this investigation, HSkMC established from severely obese individuals were found to be metabolically flexible in response to 24 h incubations with lipid, galactose, or pyruvate as evidenced by an increase in state 3 palmitoyl-carnitine malate (PCM₃) and FCCP stimulated respiration in response to all three substrates. Citrate synthase activity and OXPHOS protein content also increased whereas glucose utilization decreased in response to substrate challenges in both lean and obese groups. The volunteers in the second study were young and likely not far into the progression of metabolic disease, which may explain why metabolic flexibility remained intact in this population. Although limited by the inability to fully recapitulate true physiological conditions, human primary skeletal muscle culture is a novel tool for investigations into the mechanisms underlying metabolic inflexibility in obesity.
Keywords: Kinesiology; Metabolic flexibility; Skeletal muscle; Musculoskeletal system; Obesity; Metabolism--Disorders